Understanding the impact of internal marketing practices on both employees’ and managers’ organizational commitment in elderly care homes. - Bermúdez-González, Guillermo José; Sasaki, Innan; Tous-Zamora, Dolores (Emerald, 2016)
Purpose – The purpose of this paper is to unfold the relationship between the antecedents ofemployee and manager commitment, using internal marketing (IM) practices, in elderly care homes. Design/methodology/approach – Based on survey data drawn from elderly care homes in Finland, the authors tested several literature driven hypotheses of how IM practices (internal value exchange, internal communication and training) relate with employee and manager commitment. Hence, the authors compare the organizational commitment of two groups. Additionally, the authors tested the moderating role of public residence on these relationships. Findings – The study revealed that there are differences in the antecedents to employee and manager commitment in terms of internal value exchange. This is an important extension to the literature of employee and management commitment in which the antecedents to management commitment, especially, are under-investigated, and where the relationship between the antecedents of the two types of commitment are not studied. Practical implications – While different emphases on IM programs for employees and managers must be implemented in order to re-create work environments that could lead to improved service provision, the authors suggest that facilitating open and honest communication and exchanging values in care homes is a crucial step for improving service quality and employee and manager retention. Originality/value – This study has high value to both the literature and practice as high-service quality can be provided when both employee’s and manager’s commitments are in place, and without understanding the differing antecedents and their relationships, it is hard to establish both types of commitment in an organization. The authors believe that this new insight is useful in improving the service quality and employee and manager retention of organizations.
https://openpolicyfinder.jisc.ac.uk/id/publication/32360?from=single_hit
Keywords: Residencias de ancianos - Gestión; Psicología de las organizaciones; Recursos humanos; Manager; Organizational commitment; Antecedent; Elderly care home; Employee; Internal marketing